Pengembangan Kurikulum Operasional Sekolah Jenjang MI/SD Pasca Covid-19 - Moch. Farich Alfani; Sukiman Sukiman; Sholikin Sholikin (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
The problem of educators in the 4.0 era in making breakthroughs in the creation of innovative learning material delivery, especially after COVID-19, requires innovative solutions in teaching and learning activities in elementary schools. The curriculum developed is expected to be able to provide a pleasant learning atmosphere and educational goals will be easily achieved according to the situation and conditions in the educational unit. This study aims to analyze the operational curriculum of MI/SD schools as a reference to develop components of post-COVID-19 operational curriculum development. This research uses library research method. The results showed that the development of the operational curriculum for MI/SD schools after COVID-19 can be carried out with various principles, paying attention to the preparation references, and the preparation process.